SYNTHESIS AND CHARACTERIZATION OF HOLLOW SILICA NANOPARTICLES WITH PALLADIUM: ASSESSING GERMINATION TRAITS IN CAMELINA SATIVA L. - Masoumeh Ghorbani; Zeinab Chaghakaboodi; Danial Kahrizi (Journal of Animal and Plant Sciences, 2026)
Given the necessity of promoting and expanding the cultivation of oilseed plants, including Camelina, and the importance of assessing the effects of nanoparticles on the environment and agriculture, an experiment was conducted to evaluate the impact of different concentrations of synthesized palladium nanoparticles (0, 50, 100, and 200 mg/L) on certain germination indices of the Soheil cultivar of Camelina. These indices included germination percentage, root length, shoot length, and the root-to-shoot length ratio. In this study, hollow silica nanoparticles loaded with palladium metalwere synthesized on hollow mesoporous silica functionalized with an organic ligand (HMSNs∼Pyra/Pd). The characteristics of the palladium nanoparticles (PdNPs) were analyzedemploying Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and energy-dispersive X-ray spectroscopy (EDX). The study was designed as a completely randomized experiment with three replications under in vitro conditions.The morphology results of the nanoparticles, analyzed using TEM, indicated an average size of 30–50 nm for HMSNs∼Pyra/Pd nanoparticles and approximately 5–8 nm for palladium nanoparticles. The SEM images showed nanoparticles with an average size of around 25–35 nm, which was consistent with the TEM findings. FT-IR analysis also revealed that the signal corresponding to the asymmetric stretching vibration of the Si-O-Si bond appeared at approximately 1095 cm⁻¹. The bonds at 807 cm⁻¹ and 1468 cm⁻¹ corresponded to the symmetric stretching vibration of Si-O, confirming the presence of the SiO2 layer. The elemental analysis of the synthesized nanoparticles using EDX confirmed the presence of C, N, Si, O, and Pd in the structure of HMSNs∼Pyra/Pd nanoparticles.This confirms the successful functionalization of the hollow silica nanoparticles using this technique. The results also indicated that different concentrations of palladium nanoparticles had a significantly negative effect on all the studied germination traits of the Camelina plant. The highest germination percentage (95%) was observed in the control group, while the lowest (67.11%) was recorded at the 200 mg/L palladium nanoparticle concentration.
Keywords: Co-precipitation method; Germination Percentage; Hollow Silica Nanoparticles; Pyrazolone; Sol-gel method